Inventory of Pests on Local Potato Plants from Soe in South Central East District, Province of East Nusa Tenggara - Petronella S. Nenotek; Agnes V. Simamora; Mayavira V. Hahuly; Elias O. St. Nguru (Jurnal Penelitian Pendidikan IPA, 2022)
Sub-districts Kie and Fatumnasi are two sub-districts in mainland West Timor that cultivate local potatoes from Soe. This germplasm needs to be preserved and developed to diversify non-rice alternative food. One of the main obstacles in cultivating potatoes is the presence of pests, but so far there have been no reports of pests on local potato plants from Soe from the two sub-districts, so this research needs to be done. This study aimed at an inventory of important pests on local potato plants from Soe as a database for early detection to prevent the occurrence of explosive pests. This research was conducted on potato plantations in Fatuulan Village, Ayofanu Village, Nunleu Village, and Nenas Village. The method used is a purpose survey at a specified sample point. A sampling of insect pests is done by direct observation and insect nets. The pests found were put in a killing bottle or 70% alcohol, collected, and identified. Observation variables include the type of pest, symptoms of pest attack, and morphological characteristics of the stadia found. The data obtained were analyzed descriptively. The results showed that five species of pests damaged local potatoes from Soe. The five pests were Spodoptera litura, Henosepilachna vigintioctomaculata, Liriomyza sp, Phthorimaea operculella, and Nezara viridula. The identification results showed that in Kie District there were three pest species, namely S. litura, H. vigintioctomaculata, and Liriomyza sp. Meanwhile, in Fatumnasi District, there were four types of pests, namely H. vigintioctomaculata, Liriomyza sp, P. operculella, and N. viridula